Structured Encryption and Leakage Suppression - Kamara, Seny; Moataz, Tarik; Ohrimenko, Olya (CRYPTO, 2018)
Structured encryption (STE) schemes encrypt data structures in such a way that they can be privately queried. One aspect of STE that is still poorly understood is its leakage. In this work, we describe a general framework to design STE schemes that do not leak the query/search pattern (i.e., if and when a query was previously made). Our framework consists of two compilers. The first can be used to make any dynamic STE scheme rebuildable in the sense that the encrypted structures it produces can be rebuilt efficiently using only O(1) client storage. The second transforms any rebuildable scheme that leaks the query/search pattern into a new scheme that does not. Our second compiler is a generalization of Goldreich and Ostrovsky's square root oblivious RAM (ORAM) solution but does not make use of black-box ORAM simulation. We show that our framework produces STE schemes with query complexity that is asymptotically better than ORAM simulation in certain (natural) settings and comparable to special-purpose oblivious data structures. We use our framework to design a new STE scheme that is ``almost" zero-leakage in the sense that it reveals an, intuitively-speaking, small amount of information. We also show how the scheme can be used to achieve zero-leakage queries when one can tolerate a probabilistic guarantee of correctness. This construction results from applying our compilers to a new STE scheme we design called the piggyback scheme. This scheme is a general-purpose STE construction (in the sense that it can encrypt any data structure) that leaks the search/query pattern but hides the response length on non-repeating queries.